Preliminary application of tapered glass capillary microbeam in MeV-PIXE mapping of longan leaf for elemental concentration distribution analysis - S. Natyanun (2018)
© Published under licence by IOP Publishing Ltd. This study was aimed at understanding elemental concentration distribution in local longan leaf for how the plant was affected by the environment or agricultural operation. The analysis applied the MeV-microbeam particle induced X-ray emission (PIXE) mapping technique using a home-developed tapered glass capillary microbeam system at Chiang Mai University. The microbeam was 2-MeV proton beam in 130 μm in diameter. The studying interest was in the difference in the elemental concentrations distributed between the leaf midrib and lamina areas. The micro proton beam analyzed the leaf sample across the leaf midrib edge to the leaf lamina area for total 9 data requisition spots. The resulting data were colored to form a 1D-map of the elemental concentration distribution. Seven dominant elements, Al, S, Cl, K, Ca, Sc and Fe, were identified, the first six of which were found having higher concentrations in the midrib area than in the lamina area, while the Fe concentration was in an opposite trend to that of the others.